Phosphate Transporter Profiles in Murine and Human Thymi Identify Thymocytes at Distinct Stages of Differentiation - Machado, Alice; Pouzolles, Marie; Gailhac, Sarah; Fritz, Vanessa; Craveiro, Marco; López-Sánchez, Uriel; Kondo, Taisuke; Pala, Francesca; Bosticardo, Marita; Notarangelo, Luigi D.; Petit, Vincent; Taylor, Naomi; et al. (Frontiers in Immunology, 2020)
Thymocyte differentiation is dependent on the availability and transport of metabolites in the thymus niche. As expression of metabolite transporters is a rate-limiting step in nutrient utilization, cell surface transporter levels generally reflect a cell’s metabolic state. The GLUT1 glucose transporter is upregulated on actively dividing thymocytes, identifying thymocytes with an increased metabolism. However, it is not clear whether transporters of essential elements such as phosphate are modulated during thymocyte differentiation. While PiT1 and PiT2 are both phosphate transporters in the SLC20 family, we show here that they exhibit distinct expression profiles on both murine and human thymocytes. PiT2 expression distinguishes thymocytes with high metabolic activity, identifying immature murine double negative (CD4-CD8-) DN3b and DN4 thymocyte blasts as well as immature single positive (ISP) CD8 thymocytes. Notably, the absence of PiT2 expression on RAG2-/- thymocytes, blocked at the DN3a stage, strongly suggests that high PiT2 expression is restricted to thymocytes having undergone a productive TCR rearrangement at the DN3a/DN3b transition. Similarly, in the human thymus, PiT2 was upregulated on early post- selection CD4+ISP and TCR-CD4hiDP thymocytes co-expressing the CD71 transferrin receptor, a marker of metabolic activity. In marked contrast, expression of the PiT1 phosphate importer was detected on mature CD3+ murine and human thymocytes. Notably, the percentages of TCR thymocytes expressing PiT1 increased significantly in the aged thymus (1 year, p<0.01). Moreover, PiT1 expression on CD3+DN thymocytes was identified as a biomarker of an aging thymus, increasing from 8.41.5% to 42.49.4% by 1 year of age (p<0.0001). Thus, metabolic activity and thymic aging are associated with distinct expression profiles of the PiT1 and PiT2 phosphate transporters.